Formation of Students' Independent Research Skills and Abilities in The Learning Process - Rukhsora, Kudratullaeva (Indonesian Journal of Education Methods Development, 2019)
The article explores the views of scholars who have conducted research on the issues of vocational training, student development, and career guidance. Proposals and recommendations on the development of students' independent research skills and abilities are developed in the course of training.